Three cases of Parafilaria bovicola infection in Belgium, and a few recent epidemiological observations on this emergent disease. (2nd February 2013) - Caron, Y.; Groignet, S.; Saegerman, C.; Losson, B. J.
Abstract : Parafilariosis is a vectorborne parasitic disease caused by the development of the nematode Parafilaria bovicola in the subcutaneous and intermuscular connective tissues of cattle. On February 28, 2012, the so‐called bleeding spots were observed in two heifers and one bull in a cattle herd close to Namur (Belgium). The animals had been treated in December with an injectable ivermectin/closantel solution (Closamectin pour‐on, Norbrook Lab) at the recommended dosage. Samples of serohaemorrhagic exudate and blood, as well as skin biopsies, were collected. Embryonated eggs of P bovicola in the serohaemorrhagic exudate and high levels of creatine phosphokinase were detected. Clinically affected animals were treated with injectable ivermectin (Ivomec, Merial) at 200 μg/kg. Two epidemiological phone surveys were carried out in the south of Belgium (Wallonia) in order to estimate the geographical distribution of this condition since it was first described and published in 2009. A standardised questionnaire was used and the results were analysed. Most outbreaks were recorded in the provinces of Liege and Luxembourg. The initial source of infection is still unknown, but this parasitic infection is clearly spreading from the initial Belgian outbreak site.